Anatomy of network security execution through utilizing SPSS to evaluate public Wi-Fi - Amani Balqis Johal,; Abdulsahib, Aws A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
The increasing number of internet users has had a significant influence on the functions of Wi-Fi. Due to its extensive availability and free service, Wi-Fi has become an indispensable instrument for communication, especially among students. The continuous expansion of Wi-Fi provides an opportunity for malevolent attackers to undertake cyberattacks using public Wi-Fi as a route. Therefore, a full grasp of Wi-Fi dangers is required, which brought to this study that attempts to discuss the usage and awareness of public Wi-Fi among students. It is to study the human behaviour of students by doing the sampling of research, which involves distributing the survey questions to primary and secondary students at Alnoor International School to assess whether they are alert to the implications of using public Wi-Fi. To determine the findings of the study, chart forms are used. It showed that most students are aware of how dangerous public Wi-Fi can be, but they don't know enough about security to know how to protect themselves from potential dangers and threats from hackers.